Koreans in Iloilo City their lifestyles, social-psychological and cultural adjustment - Cabangal, Joann
This study sought to know the sociodemographic characteristics, lifestyle, social-psychological, and cultural adjustment of Korean visitors in Iloilo City, who were currently enrolled in Moohan Tutorial Service, Inc., The results showed that Koreans in Iloilo City are generally single with ages ranging from 20 to 30 years old and dependent on the allowances they receive from their parents or guardian monthly. The study also showed that Koreans in Iloilo City are relatively well adjusted in their life in the Philippines, which is manifested in their improved social interaction with the locals of Iloilo City. at the same time, they are generally well off as reflected on their spending patterns as compared to the Filipinos' standard of living. They relatively spend more than an average Filipino would spend for food, transportation, clothing and many others for a certain period of time.